Community Service Activity in Banyuwangi Preparing Future Leaders: Life Skills and Leadership Development for University Students - Annisa Parastry; Dewi Lusiana; Muhammad Ramaditya; Abdurrahman (Institut IPMI, 2025)
In response to the growing need for youth empowerment in Indonesia’s rural areas, this community engagement initiative was carried out at SMA Negeri 1 Glagah, Banyuwangi, targeting 11th-grade students preparing for higher education. The program aimed to strengthen students’ life skills and leadership capacities as foundational tools for personal growth and future academic success. Through interactive workshops and reflective exercises, participants explored key themes such as problem-solving, communication, teamwork, critical thinking, and adaptability. Designed with participatory and experiential learning methods, the program encouraged active student involvement and ensured contextual relevance to their social environment. Initial feedback indicated that students felt more confident, motivated, and better equipped to navigate the transition to university life and take on future leadership roles. This article presents the design, implementation, and outcomes of the initiative, offering a replicable model for youth development programs in similar educational and community settings.